1977
DOI: 10.1128/iai.18.3.586-595.1977
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Microflora and Physiology of the Anterior Intestinal Tract of Pigs Weaned at 2 Days, with Special Reference to the Pathogenesis of Diarrhea

Abstract: The gastrointestinal microflora and gastric physiology of piglets weaned at 2 days was compared with that of piglets allowed to continue sucking the sow. Although there was a significantly higher count of Escherichia coli in the stomach, duodenum, and jejunum of the early-weaned compared with sow-reared pigs, these differences were not detectable in samples from the ileum. There were no quantitative differences in lactobacilli and in streptococci between the two treatments. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0

Year Published

1978
1978
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(18 citation statements)
references
References 34 publications
1
17
0
Order By: Relevance
“…Given the high gastric pH that is usually observed post-weaning, gastric stasis may contribute to development of PWD in piglets by allowing proliferation of pathogenic bacteria. Indeed, gastric stasis has been documented in early-weaned pigs as a contributing factor for PWD (White et al, 1969;Barrow et al, 1977). In addition, it has been reported that a stress gene, corticotrophin-releasing factor receptor 2, whose activation has been implicated in the inhibition of gastric motility (Martinez et al, 2004), is up-regulated in the jejunum of weaned pigs (Moeser et al, 2007).…”
Section: Stomachmentioning
confidence: 99%
“…Given the high gastric pH that is usually observed post-weaning, gastric stasis may contribute to development of PWD in piglets by allowing proliferation of pathogenic bacteria. Indeed, gastric stasis has been documented in early-weaned pigs as a contributing factor for PWD (White et al, 1969;Barrow et al, 1977). In addition, it has been reported that a stress gene, corticotrophin-releasing factor receptor 2, whose activation has been implicated in the inhibition of gastric motility (Martinez et al, 2004), is up-regulated in the jejunum of weaned pigs (Moeser et al, 2007).…”
Section: Stomachmentioning
confidence: 99%
“…In pigs and most monogastric animals, the stomach and small intestine are dominated by Lactobacillus and Streptococcus spp., with generally higher cell numbers (10 7 -10 9 CFU ml )1 ) in the small intestine (Fuller et al 1978;Conway 1989). The main role of these organisms is to produce lactic acid to maintain a low stomach pH (Cranwell et al 1976;Barrow et al 1977). The most prevalent species in the porcine digestive tract are Lactobacillus acidophilus, Lactobacillus delbrückii, Lactobacillus fermentum, Lactobacillus reuteri, Lactobacillus salivarius, Enterococcus bovis, Enterococcus durans, Enterococcus faecalis, Enterococcus faecium, Streptococcus intestinalis, Strep-tococcus porcinus, Streptococcus salivarius, Bifidobacterium adolescentis and Bifidobacterium suis (Raibaud et al 1961;Zani et al 1974;Barrow et al 1977;Fuller et al 1978;Collins et al 1984;Robinson et al 1984Robinson et al ,1988.…”
Section: Introductionmentioning
confidence: 99%
“…The main role of these organisms is to produce lactic acid to maintain a low stomach pH (Cranwell et al 1976;Barrow et al 1977). The most prevalent species in the porcine digestive tract are Lactobacillus acidophilus, Lactobacillus delbrückii, Lactobacillus fermentum, Lactobacillus reuteri, Lactobacillus salivarius, Enterococcus bovis, Enterococcus durans, Enterococcus faecalis, Enterococcus faecium, Streptococcus intestinalis, Strep-tococcus porcinus, Streptococcus salivarius, Bifidobacterium adolescentis and Bifidobacterium suis (Raibaud et al 1961;Zani et al 1974;Barrow et al 1977;Fuller et al 1978;Collins et al 1984;Robinson et al 1984Robinson et al ,1988. Migration of pH and bile resistant strains to the larger intestine ensures a healthy balance between probiotic strains and opportunistic pathogens (Fuller et al 1978;Dunne 2001;Ohashi et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Lactobacilli are numerous in the digestive tract of pigs, constituting one of the principal bacterial groups inhabiting proximal regions of the tract (1). Some of these lactobacilli have the ability to colonize the epithelial surface lining the porcine esophagus and part of the stomach (the pars oesophagea), forming relatively thick bacterial layers (5,13).…”
mentioning
confidence: 99%